Epidemiologia da Sífilis gestacional e congênita no extremo Setentrional da Amazônia - Lins, Cynthia Dantas de Macedo (2014)
Syphilis is the disease caused by Treponema pallidum pallidum disease. When transmitted by placenta during pregnancy can lead to congenital syphilis, providing an increase in fetal morbidity such as premature birth and learning disabilities, among others. There was a high number of cases in Roraima between 2008 and 2011, compared what is recommended by the Ministry of Health, without clarification on the profile of pregnant women with syphilis. Thus, the aim of this cross-sectional study was to analyze the epidemiology of gestational and congenital syphilis in Maternal Infant Hospital Nossa Senhora de Nazaré (HMINSN). The study was conducted in Roraima, Brazilian state located in the northern reaches of the Amazon. The research subjects were the mothers of HMINSN, only public maternity Roraima, during the period November 2012 to June 2013. Antenatal care visit cards exams and VDRL exams from the medical records were identified during the survey period and selected those who had positive VDRL in the Antenatal care visit Card and/or in hospitalization to be interviewed, for using data analysis the 95% CI (Confidence Index) and qui-square test (χ²) with significance de p<0.05 . The project was approved by the Ethics Committee on Research of Universidade Federal de Roraima (COEP UFRR) (protocolo121001). It were identified 4,142 prenatal cards and medical records, selected 44 cases of positive VDRL and made 37 (86.04 %) interviews were analyzed. There was an incidence of 10.3 cases of gestational syphilis/1000 Live Births (LB) and 8.4 cases of congenital syphilis/1000 LB. The results showed statistical significance (p < 0.05), demonstrated a predominance of the group aged 20 to 34 years (66.44 %), mulatto (74.42%), with primary level (58.14%), with family income up to 1 minimum wage (69.44%), coming from Boa Vista (74.42%), located mainly in the west and south of the city, with less than 7 prenatal visits and achievement of 2 or more VDRL tests. The partners of the mothers with congenital syphilis did not undergo treatment (78.7%) and did not use condom as a barrier method for syphilis prevention (63.6%). There were 24.24% preterm and 6.06 % of stillborn among newborns with congenital syphilis. We conclude that educational measures for patients and their partners, and training programs for health professionals should be performed in order to reduce the high number of existing congenital syphilis in Roraima.